Risk selection in primary care: a cross-sectional fixed effect analysis of Swedish individual data - Ulrika Winblad; David Isaksson; Paula Blomqvist; Ronnie Pingel (BMJ Open)
Objective To assess socioeconomic differences between patients registered with private and public primary healthcare centres.Design Population-based cross-sectional study controlling for municipality and household.Setting Swedish population-based socioeconomic data collected from Statistics Sweden linked with individual registration data from all 21 Swedish regions.Participants All individuals residing in Sweden on 31 December 2015 (n=9 851 017) were included in the study.Primary outcome measures Registration with private versus public primary healthcare centres.Results After controlling for municipality and household, individuals with higher socioeconomic status were more likely to be registered with a private primary healthcare provider. Individuals in the highest income quantile were 4.9 percentage points (13.7%) more likely to be registered with a private primary healthcare provider compared with individuals in the lowest income quantile. Individuals with 1–3 years of higher education were 4.7 percentage points more likely to be registered with a private primary healthcare provider compared with those with an incomplete primary education.Conclusions The results show that there are notable differences in registration patterns, indicating a skewed distribution of patients and health risks between private and public primary healthcare providers. This suggests that risk selection behaviour occurs in the reformed Swedish primary healthcare system, foremost through location patterns.